Escolhas poss??veis em futuros incertos: a escola e a constru????o do projeto de vida profissional na adolesc??ncia - Silva, Alexandre Bernardo da (2017)
The objective of this research is to understand the project of professional life of adolescents in high school and it was constituted as a research problem to understand the role of the school in the construction of these projects. The hypothesis for the research problem presupposes that: a) the school does not directly determine the professional choice, however, the professional life projects of the adolescents are influenced by the school, according to the pedagogical proposals or projects inserted in their daily school life; B) students in private schools tend to build their professional life projects that are more often targeted at careers requiring higher education, unlike public school students. The general objective is to reflect on the influence of the school in the construction of the professional life projects of adolescents at the end of High School, in order to investigate, specifically as two schools, one public and another private, located in the same region and frequented by students Of similar socioeconomic conditions, influence these projects and collaborate directly or indirectly in the future professional choices of these adolescents. The theoretical-critical referential is found in the critical theory of the Frankfurt School, especially Adorno, Marcuse and Horkheimer, and in the light of this reference, the concepts of formation and work in contemporary society are discussed. The methodology of empirical research consisted of the application and analysis of a socioeconomic questionnaire and the accomplishment of two focus groups with students enrolled in the third year of regular high school in the daytime period of a public and a private school in the city of S??o Paulo. After analyzing the interviews, the main results indicated that the hypotheses were confirmed, thus, the school influence the projects of professional life of the adolescent to the extent that adopts a model of education and training, permeated by discourses that qualify or disqualify the institutions offering Elements that lead adolescents to identify themselves with the possibility or not of practicing certain professions.